Development and Characterization of Polyamide Fiber Composite Filled with Fly Ash for Wind Turbine Blade. - Joy Mathavan, J.; Patnaik, A. (Springer Nature Singapore, 2020)
Proposing a suitable material for wind turbine blade is discussed in this paper. Low weight, high stiffness, high strength, and long durability are some of the salient features a material should possess to act as the wind turbine blade. Carbon fiber, glass fiber, and aramid fiber are used as blade materials in these days because they meet most of these features. In addition to, fly ash as filler material with polyamide fiber is discussed in this paper. The specimens were prepared by hand layup process. Erosion test is performed in air-jet erosion tester. The graphs are drawn according to smaller the better criteria of Taguchi L25 orthogonal array of two factors and five variables. Graphs obtained from dynamic mechanical analyzer for tensile test and three-point bending test are compared for different specimens. Hardness values are calculated by Rockwell hardness tester, and densities are calculated to analyze the void content.
Keywords: Aramid fiber; Fly ash; Tensile strength; Wind turbine blade